Silkworm and Silk: Traditional and Innovative Applications - Cappellozza, Silvia; Casartelli, Morena; Sandrelli, Federica; Saviane, Alessio; Tettamanti, Gianluca (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Papers collected in the present Special Issue relate to the field of sericulture. They cover different aspects based on a very ancient human agricultural activity, taking into consideration classical agronomic aspects, such as the impact of feeding on silk quality and sericulture in different parts of the world. Nonetheless, cutting edge topics are addressed as well, with papers studying silk as a biomaterial, the silkworm as a model organism, and the possibility of exploring its physiology and the molecular mechanisms that stand behind it with the aid of modern tools such as gene profiling, the CRISPR/Cas-9 system, and -omics sciences.